In Vitro Evaluation of Seaweed for Digestibility and Methane Production - Katwal, Sarishti; Trivedi, Manojkumar Motibhai; Pandya, Paresh Ratilal; Bhavsar, Maitri Yogeshkumar; Prajapati, Dharmesh Thakorbhai (Indian Journal of Animal Nutrition, 2020)
The study was conducted to evaluate effect of seaweed (Sargassum johnstonii) in Total Mixed Ration on in vitro digestibility and methane production. Different TMRs were formulated using concentrates and wheat straw in ratio of 60:40 and used as basal diet. Seaweeds were incorporated @ 0, 2, 4, 6, 8 and 10 % level and incubated for 24 hours for in vitro studies. There was no significant difference in in vitro methane and DM digestibility among all groups. However, highest reduction in in vitro CH4 production in terms of ml/100 mg DM (2.71Â±0.09) and ml/100 mg DDM (2.25Â±0.07) was found at 8% level which was 9.66 and 10.71 % less respectively as compared to control. The study revealed that seaweeds have potential to mitigate methane emission in ruminants.